2022
DOI: 10.1177/00031348221102604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Chemoprophylaxis in Traumatic Brain Injury and Risk of Venous Thromboembolism

Abstract: Background The optimal timing to initiate venous thromboembolism (VTE) prophylaxis in patients with a traumatic brain injury (TBI) is still unknown. We designed a study to determine the effect that timing of initiation of VTE prophylaxis has on VTE rates in TBI patients. Methods Patient records were obtained from 32 level 1 and 2 trauma centers in the Michigan Trauma Quality Improvement Program from 2008 to 2018. Overall, 5589 patients with a TBI were included and split into cohorts based on VTE prophylaxis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…They showed that early (< 24 hours) administration was not associated with ICH progression 15 . Similar reductions in VTE rates were also observed and reported by Scudday, Saadeh, Rivas, Shulkosky 16,17,18,19 .…”
Section: Discussionsupporting
confidence: 87%
“…They showed that early (< 24 hours) administration was not associated with ICH progression 15 . Similar reductions in VTE rates were also observed and reported by Scudday, Saadeh, Rivas, Shulkosky 16,17,18,19 .…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study by Shulkosky et al utilizing the TQIP database, authors explored the influence of different VTE prophylaxis initiation timeframes on the incidence of VTE within TBI patients, finding that patients who underwent VTE prophylaxis initiation within the intervals of 48 to 72 hours and beyond 72 hours after admission had higher odds of experiencing VTE occurrences in contrast to patients with administration within the initial 24 hours. 9 Our study supports this evidence, as analysis showed that patients who received late prophylaxis after 24 hours had significantly higher rates of DVT and PE compared to patients who received it early before 24 hours across all racial groups and independent of injury type. While the work by Shulkosky et al showed the benefit of early VTE prophylaxis in reducing VTE incidence within the TBI patient cohort, our investigation highlights that this finding is consistent across racial groups and injury types, additionally underscoring the necessity for individualized strategies that accommodate diverse patient attributes to yield optimized clinical outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…While the work by Shulkosky et al showed the benefit of early VTE prophylaxis in reducing VTE incidence within the TBI patient cohort, our investigation highlights that this finding is consistent across racial groups and injury types, additionally underscoring the necessity for individualized strategies that accommodate diverse patient attributes to yield optimized clinical outcomes. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation